How Do Friendships Form? - Marmaros, D.; Sacerdote, B. (Quarterly Journal of Economics, 2006)
We examine how people form social networks among their peers. We use a unique data set that tells us the volume of email between any two people in the sample. The data are from students and recent graduates of Dartmouth College. First-year students interact with peers in their immediate proximity and form long-term friendships with a subset of these people. This result is consistent with a model in which the expected value of interacting with an unknown person is low (making traveling solely to meet new people unlikely), while the benefits from interacting with the same person repeatedly are high. Geographic proximity and race are greater determinants of social interaction than are common interests, majors, or family background. Two randomly chosen White students interact three times more often than do a Black student and a White student. However, placing the Black and White student in the same freshman dorm increases their frequency of interaction by a factor of three. A traditional “linear in group means” model of peer ability is only a reasonable approximation to the ability of actual peers chosen when we form the groups around all key factors including distance, race and cohort.